Development of a Real-Time Inventory Management System Using Waterfall Model for Micro and Small Enterprises: A Case Study of Toko Karomah - M. Aghis Sufiantoro Saputra; Agung Brastama Putra; Prasasti Karunia Farista Ananto (Universitas Islam Kuantan Singingi, 2026)
Micro and Small Enterprises (MSEs) often struggle with warehouse and inventory management due to manual recording processes, limited system integration, and the absence of real-time stock visibility. These challenges contribute to stock inaccuracies, delayed restocking decisions, and operational inefficiencies. This study develops a real-time Warehouse Management System (WMS) using the Laravel framework to support the operational activities of Toko Karomah, a small retail business in East Java, Indonesia. The system integrates core features such as item master data, stock-in and stock-out modules, user role management, and real-time stock updates supported by reorder point thresholds. The development process follows the Waterfall methodology, covering requirements analysis, system design, implementation, testing, and deployment. The results show that the system effectively improves stock accuracy, reduces the risk of stock-outs, and enhances workflow efficiency. User Acceptance Testing (UAT) confirms that the system meets functional and usability requirements. This research demonstrates that a Laravel-based real-time WMS can significantly support digital transformation for MSEs, especially in inventory-critical operations.